The magic of dialogue transforming conflict into cooperation - Yankelovich, Daniel (Simon & Schuster, 1999)
"In The Magic of Dialogue, social scientist Daniel Yankelovich does more than revive the ancient art of dialogue; he reinvents it in a brief, practical form that suits our times. Drawing on decades of research, he offers a method that will help managers, leaders, businesspeople, and other professionals succeed in the new economy. By helping them to master the communication skills needed to conduct dialogue successfully, he shows how the discipline of dialogue can make them more effective managers, strengthen relationships, resolve problems, and achieve shared objectives."--Jacket.